Growth Performance, Mortality, Relative Organ Weight, Blood Biochemistry, and Intestinal Microbial of Arbor Acres Broiler Fed Diets Containing Mannan-Riched Fraction (Mrf) and Probiotic-Enhanced Liquid Acidifier - Danung Nur Adli; Osfar Sjofjan (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The research purpose was to carry out the effect of mannan-riched fraction (MRF) and probiotic enhanced water as natural growth promoters (NGPs) on Growth Performance, mortality, relative organ weight, blood biochemistry, and intestinal microbial flora. A total of 3000 day old chicks (DOC) Arbor Acres broiler were randomly allocated to 4 dietary treatments and 4 replications of 187 broilers per cage. Four treatments used in research were as follows: i) CON, basal diet, ii) basal diet, CON+ MRF (Actigen™) 80g/100kg/feed , iii) basal diet, CON+ 0.2% drinking water + 2 ml/L Combination feed additive (Acid-Pak 4-way®), and iv) ) basal diet, CON+ MRF (Actigen™) 80g/100kg/feed+ drinking water 2 ml/L Combination feed additive (AcidPak 4-way®). The results showed that using mannan riched fraction (MRF) (feed) and combination with probiotic-enhanced liquid acidifier (drinking water) presented significant difference (P>0.05) on body weight gain at 1-28 days and intestinal microbial. On the blood biochemistry, the effect of combination began to reduce the amount of glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) at 21 days periods. To sum up, the addition of mannan-riched fraction and combination with probiotic enhanced liquid acidifier doesn’t impacted on growth Growth Performance, blood biochemistry, relative organ weight but give significant effect on intestinal microbial and reduces mortality of broiler.